Design Build Finding EO as A Web-Based Marketplace Event Organizer and Venue Apps - Husein, Muhammad; Gede Dwidasmara, Ida Bagus (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2020)
Event in Indonesia is an activity that utilizes a place or service in the implementation of these activities. Many obstacles that currently often occur when an event wants to be held either in the limited availability of information about the Event Organizer or where the event is inadequate due to limited sources. The similar information provided only display Event Organizer or Venue, but this is limited by the absence of a system that fulfills the transaction process directly. In the era of the development of science and technology as well as industry 4.0 that continues to expand, business ideas emerge that are initialized into one of the web-based marketplace application platforms that are able to promote Event Organizer and Venue also provide information and Event Organizer and Venue ordering processes for Event Users. The system, entitled Finding EO, uses the Prototyping method and its developed with PHP Programming languages.